Mapping Business Transformation in Digital Landscape: A Prescriptive Maturity Model for Small Enterprises - Juhani Naskali; Jesse Kaukola; Johannes Matintupa; Hanna Ahtosalo; Mikko Jaakola; Antti Tuomisto (Switzerland, 2022)
Developing versatile modern ICT is an insurmountable challenge to many small and medium enterprises (SMEs). Resources, such as skills, money, time [1] and knowledge [2], are scarce [3]. This makes the selection and decision of any development project a key business issue. The most important questions for SMEs are (i) where to start and (ii) what to change. While there are hundreds of descriptive maturity models for organizational development [4, 5], these offer little support for organizational decision-making. We developed a prescriptive maturity model that maps a subjective snapshot of the maturity of a business, and identifies the most promising objects for next development steps. This Business Transformation Map has three interrelated maturity dimensions: business, technology, and social, that span across past, present and future. We used the model in several test cases, and our results show that the model makes business dimensions visible in a way that makes sense to SMEs. The interviewed SME companies state that depicting company maturity levels in this manner brings clarity to overall business growth options, and it helps transforming this understanding into concrete development steps.
Well-Being in the Information Society. Fighting Inequalities